The design optimisation of an insect-inspired micro air vehicle - Conn,AT; Burgess,SC; Ling,CS; Vaidyanathan,R (International Journal of Design and Nature and Ecodynamics, 2008)
Insect-inspired micro air vehicles (MAVs) have been the subject of extensive research in recent years for a range of novel applications. The current generation of vehicles, however, has yet to match even a fraction of the performance of insect flight, in particular with respect to manoeuvrability and payload capacity. Precise reproduction of insect-like flapping motion on the micro-vehicle scale holds significant potential to address this deficiency. The design and optimisation of this critical aspect of an insect-inspired MAV is the subject of this paper. The actuated flapping mechanism must deliver a high power output via complex wing kinematics, which should be dynamically adjustable for controlled flight without the need for traditional control surfaces. This paper first addresses several key flapping MAV design criteria that greatly influence the power requirements and aerodynamic forces for flight, through an assessment of design parameters such as wing length and wingbeat frequency. Two solutions are then proposed that meet these requirements while satisfying the current limitations of miniature actuation technologies and issues related to mechanism constraint. The first of these, the development of an artificial muscle actuator is crucial to the feasibility of a highly adjustable, lightweight under-constrained flapping mechanism. A prototype artificial muscle based on a silicone dielectric elastomer was tested and found to produce a strain output comparable to muscle. We also report the development of an alternative flapping mechanism solution utilising conventional rotary DC motors. The novel parallel crankrocker (PCR) mechanism produces similar wing kinematics to insects and, unlike previously developed DC motor-driven MAV flapping mechanisms, it allows dynamically adjustable control of the wing angle of attack. Aerodynamic testing of a PCR prototype found that it produced a maximum lift force of 6.4 g per wing pair at a wingbeat frequency of 13.2 Hz. Wind